Provision of chlamydia testing, and training of primary health care staff about chlamydia testing, across four European countries - Uusküla, Anneli (BMC Public Health, 2014)
BACKGROUND: The objectives of this study were to describe and compare chlamydia testing provided by general practitioners (GPs) in four selected European countries with well-developed primary health care systems and high reported chlamydia rates; we aimed to compare contrasting countries where chlamydia testing is provided by GPs (England, Sweden) with countries where primary care chlamydia testing is absent or very limited (France, Estonia). METHODS: For data generation a structured questionnaire was developed and secondary data sources were searched. The questionnaire developed by the research team allowed a systematic approach to analysing chlamydia care (including testing in general practice) and the gathering of relevant data. RESULTS: There were no significant differences in the burden of the disease or the type of general practice care provision in the study countries. In all four countries, testing for chlamydia (with nucleic acid amplification test, NAAT) is available in the public sector, a substantial proportion (>60%) of young people aged 16–25 years visit their general practitioner (GP) annually, and reimbursement for chlamydia testing costs to the relevant parties (GPs in England, Sweden and Estonia; and patients in France) by the national health insurance system or its equivalent. In countries where chlamydia testing is provided by GPs (England, Sweden) a national strategy or plan on STI control that specifically mentions chlamydia was in force, chlamydia care guidelines for GPs were in place and STI management was more firmly established in the GP residency training curriculum, either formally (England) or informally (Sweden), than in the other countries. CONCLUSION: Future research on the effectiveness of chlamydia screening (also in the context of general practice care) and program provision should reflect national needs and the prevention of complications. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2458-14-1147) contains supplementary material, which is available to authorized users.